PENERAPAN TEKNOLOGI PRODUKSI BERSIH UNTUK LIMBAH CAIR PADA INDUSTRI KERTAS PT. IKPP PERAWANG (Jurnal Kajian Lingkungan, 2013)
Paper industries produce waste waterin process, where waste produce dharm to the environment. Sowe need the concept of cleaner production in the paper industry. Result sof the study in the paper industry PT. IKPP Perawang there are several sources of waste water out put in the paper making proces, the unit reject the cleaner, wirepress, pressparts, machine screen and broketank. After the application of cleaner production options by applying the concept of recycle and reusewaste water on the out put source, the obtained value of total suspended solid sand fiber contentreduction. The results of the TSS value of 1,012.98 mg/L to 256.59 mg/L and the fiber contentisof 552. 77 mg/L to 157.35 mg/L. other than that there is adecrease in water consumption of 12 ton/ton of paper to 8 ton/ton of paper. From there sults of the economic analysis with the application of cleaner production in the paper industry PT.IKPP Perawang companies will profit Rp.29.844.777.600/yearsKeyword: Clean Production, recycle and reuse wastewater, total suspended solid, fiber content, water